In Vivo Interleukin-13-Primed Macrophages Contribute to Reduced Alloantigen-Specific T Cell Activation and Prolong Immunological Survival of Allogeneic Mesenchymal Stem Cell Implants. (28th March 2016) - Hoornaert, Chloé J.; Luyckx, Evi; Reekmans, Kristien; Dhainaut, Maxime; Guglielmetti, Caroline; Le Blon, Debbie; Dooley, Dearbhaile; Fransen, Erik; Daans, Jasmijn; Verbeeck, Louca; Quarta, Alessandra; De Vocht, Nathalie; et al.
Abstract: Transplantation of mesenchymal stem cells (MSCs) into injured or diseased tissue—for the in situ delivery of a wide variety of MSC-secreted therapeutic proteins—is an emerging approach for the modulation of the clinical course of several diseases and traumata. From an emergency point-of-view, allogeneic MSCs have numerous advantages over patient-specific autologous MSCs since "off-the-shelf" cell preparations could be readily available for instant therapeutic intervention following acute injury. Although we confirmed the in vitro immunomodulatory capacity of allogeneic MSCs on antigen-presenting cells with standard coculture experiments, allogeneic MSC grafts were irrevocably rejected by the host's immune system upon either intramuscular or intracerebral transplantation. In an attempt to modulate MSC allograft rejection in vivo, we transduced MSCs with an interleukin-13 (IL13)-expressing lentiviral vector. Our data clearly indicate that prolonged survival of IL13-expressing allogeneic MSC grafts in muscle tissue coincided with the induction of an alternatively activated macrophage phenotype in vivo and a reduced number of alloantigen-reactive IFNγ- and/or IL2-producing CD8 + T cells compared to nonmodified allografts. Similarly, intracerebral IL13-expressing MSC allografts also exhibited prolonged survival and induction of an alternatively activated macrophage phenotype, although a peripheral T cell component was absent. In summary, this study demonstrates that both innate and adaptive immune responses are effectively modulated in vivo by locally secreted IL13, ultimately resulting in prolonged MSC allograft survival in both muscle and brain tissue. Abstract : Upon transplantation of IL13-engineered MSCs into allogeneic mice, local IL13 production modulated both innate and adaptive immune responses, ultimately resulting in prolonged MSC allograft survival. (A): FVB mouse-derived MSC-Luc/eGFP and MSC-Luc/eGFP/IL13 implants in the muscle or brain of C57BL/6 mice. Expression of Arg1, a marker of alternative M2a activation, was restricted to F4/80+ macrophages infiltrating IL13-producing MSC grafts. (B): T cells from naive, FVB MSC-transplanted or FVB MSC-IL13-transplanted C57BL/6 mice were analyzed by flow cytometry, with or without prior FVB MSC stimulation. IL13-expressing MSC allografts induced significantly fewer alloreactive CD8+ T cells than wildtype MSC allografts. *p<0.05; ***p<0.001 (C+D): Quantitative analysis of in vivo bioluminescence imaging of intramuscular (panel C) and intracerebral (panel D) FVB MSC-Luc/eGFP or FVB MSC-Luc/eGFP/IL13 allografts in C57BL/6 mice. Background radiance is demarcated by the gray area. IL13-expressing MSC allografts display a prolonged survival in both muscle and brain tissue of immune competent mice. **p<0.01 Abbreviations: MSC, mesenchymal stem cell; IL13, interleukin-13; Luc, firefly luciferase; eGFP, enhanced green fluorescent protein; Arg1, arginase-1.